Language and Power: How News Media Construct a Biased Structure of Information in Public Discourse during the Presidential Election - Zurriyati Zurriyati; Fadhlur Rahman; Mohammed H. Alaqad (Master Program of Sociology, Universitas Malikussaleh,, 2023)
Democracy relies on public discourse to shape public opinion and influence political choices. However, political interference in reporting, as seen in media such as Media Indonesia and CNN Indonesia, has distorted public discourse and has become a serious problem. This study aimed to explore how reporting during the Indonesian presidential election is influenced by the close relationship between political parties and media authorities. This study also aims to find patterns of bias and polarization. Three methodologies were used in this research to address the problem: content analysis, comparative analysis, and intertextuality analysis. The results of this study revealed: Based on the analysis of the content of Media Indonesia's coverage, there is a clear bias towards one of the presidential candidates, which indicates political interference in the reporting. Comparative analysis reveals significant variations in news reporting approaches between Media Indonesia and CNN Indonesia, underscoring the possible impact of political players on media organizations. The use of extra textual evidence by authors to build credibility and support the stories presented is shown through an analysis of intertextuality. This study also highlights the negative effects of political interference in news coverage and its effect on public debate. The quest for universal truth is hampered by politicized and biased portrayals of topics in the media, which limit public understanding of complex issues. This study highlights the need for a free and independent press to fight these distortions, especially in fighting the domination of powerful interests.